2003
DOI: 10.1002/nau.10148
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the function of the female urethra: I: Relation between maximum urethral closure pressure at rest and urethral hypermobility

Abstract: Urethral closure pressure falls significantly when urethral hypermobility is present. This decrease is not related to patient's age or parity. Our observations demonstrate an inverse relation between urethral closure pressure and the degree of cysto-urethrocele. As hypermobility increases, closure pressure decreases, even if this decrease does not reach the level of statistical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
0
18
2
Order By: Relevance
“…In relation to age groups, that decrease occured always in SUI women, in all women in the middle age group and in women with stress or mixed incontinence in the oldest group. The decrease of MUCP during stress profi le (P3) could be related to a urethral hypermobility as it has been demonstrated by Schick et al (26). The difference between the middle age and the oldest group could be the consequence of a more rigid urethra due to oestrogen defi ciency or pelvic surgery or both.…”
Section: Discussionmentioning
confidence: 75%
“…In relation to age groups, that decrease occured always in SUI women, in all women in the middle age group and in women with stress or mixed incontinence in the oldest group. The decrease of MUCP during stress profi le (P3) could be related to a urethral hypermobility as it has been demonstrated by Schick et al (26). The difference between the middle age and the oldest group could be the consequence of a more rigid urethra due to oestrogen defi ciency or pelvic surgery or both.…”
Section: Discussionmentioning
confidence: 75%
“…We have already demonstrated that MUCP decreases with statistical signi¢cance when urethral hypermobility appears [Schick et al, 2003a]. This decrease is not in£uenced by the age or number of pregnancies of our patients.…”
Section: Discussion and Overviewmentioning
confidence: 51%
“…In the ¢rst part of this study [Schick et al, 2003a], we explored the relationship between maximum urethral closure pressure and hypermobility of the urethra. We concluded that MUCP drops signi¢cantly with the appearance of hypermobility, but that the ensuing aggravation of this hypermobility has only a marginal e¡ect on MUCP.…”
Section: Introductionmentioning
confidence: 99%
“…MUCP and cough LPP evolve ''in tandem'': a decrease in one entails a decrease in the other. In the ¢rst part of our study [Schick et al, 2003] we suggested that the partial denervation of the pelvic £oor muscles was the cause of the decrease in MUCP found with urethral hypermobility. This would imply a strictly neuro-muscular phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study [Schick et al, 2003] we analyzed the relation between maximum urethral closure pressure (MUCP) and the degree of urethral hypermobility. We concluded from that study that MUCP decreases signi¢cantly when urethral hypermobility appears.…”
Section: Introductionmentioning
confidence: 99%